PENGARUH PELATIHAN DAN MODAL BERGULIR BAZNAS (BADAN AMIL ZAKAT NASIONAL) JAWA TIMUR TERHADAP PENDAPATAN USAHA MUSTAHIQ - Fadhilah Fadhilah; Tika Widiastuti (al-Uqud : Journal of Islamic Economics, 2018)
This research aims to analyze the effect of trainig and rolling capital of BAZNAS in East Java on operating revenue of mustahiq both partially and simultaneously. It uses quantitative approach method. Sampling technique used is non-probability sampling with purposive sampling technique which is a technique of sample determination with certain consideration. Data collecting techniques used are questionnaire, interview, observation and documentation. Data analysis technique used is multiple linear regression analysis. The result processed by SPSS progeam version 23.0 for Windows shows that the value of Adjusted R Square of 0,711 means that 71,1% of operating revenue of mustahiq in BAZNAS East Java is influenced by the training and rolling capital.